Breaking barriers in accessing and uptaking climate change adaptation information by smallholder tomato farmers in Tanzania - Siyao, P.O; Sanga, E.E. (© Emerald Publishing Limited- Global Knowledge, Memory and Communication © Emerald Publishing, 2024)
Purpose – This study aims to assess barriers in accessing and uptaking climate change adaptation information among smallholder tomato farmers in Tanzania. Design/methodology/approach – This study was conducted in Iringa and Morogoro regions, Tanzania. It adopted cross-sectional research design.Multistage, purposive and randomsampling techniques with a sample size of 183 smallholder tomato farmers were used. Questionnaires containing closed- and open-ended questions, interview guide and focus group discussions were used to collect data. To ensure validity and reliability of data collection instruments, pretesting of the questionnaires was conducted by administering them to a small group of smallholder tomato growers. Statistical Product and Service Solutions software was used to analyse quantitative data while NVivo was used for analysing qualitative data. Findings – Lack of clear understanding of climate change information (132, 72.1%), scarcity of libraries and information centres (125, 68.3%), inadequate income (125, 68.3%), lack of trust of sources of information (114,62.3%), lack of sufficient knowledge about climate change (111, 60%), illiteracy (110,60.1%), poor distribution of electricity in rural areas (109, 59.6%) and use of jargons (93, 50.8%) in explaining climate change adaptation issues are hindrances for smallholder tomato farmers to access and uptake climate change adaptation information. Research limitations/implications – This study was conducted in only two districts in Tanzania; thus, the findings cannot be generalized. Practical implications – The government and relevant agencies are recommended to use appropriate strategies for breaking the barriers that impede easy access and uptake of climate change adaptation information by smallholder tomato farmers as one of the interventions to combat the impacts posed by climate change. Social implications – This study has contributed to the ongoing discourses on climate change issues. Such discourses have influenced attention and understanding of the role of access and uptake of climate change adaptation information by smallholder farmers for planning and implementation of adaptation strategies through awareness creation. Originality/value – This study is in line with goal number 13.3 of Sustainable Development Goals, which vows on taking necessary actions in combating climate change and its impacts. Thus, smallholder tomato farmers’ awareness about climate change through access and uptake of climate change adaptation information is one of the interventions to combat climate change and its impacts.